Trading Volume Activity Memediasi Hubungan Perubahan Tarif Pajak Penghasilan Badan terhadap Return Saham - Wardani, Ni Nyoman Sri; Budiartha, I Ketut (E-Jurnal Akuntansi, 2021)
Stock returns can describe the acquisition of returns on the buying and selling activities of shares carried out by investors.  The rate of returns are received by investor can be influenced by elements from outside the company. This study aims to determine the reaction of the capital market as a result of changes in corporate income tax rates in 2020 on stock returns with trading volume activity as an intervening variable.  The location of this research is in the Indonesia Stock Exchange by using 45 samples of companies obtained through the purposive sampling method.  The data is taken by documentation method.  The analysis technique used is path analysis with the single test as the final test.  Based on the test results, the changes in corporate income tax rates have a positive effect on trading volume activity.  Trading volume activity has a positive effect on stock returns.  Changes in corporate income tax rates have a positive effect on stock returns.  And trading volume activity can be an intervening variable in changes in corporate income tax rates on stock returns. Keywords: Stock Returns; Trading Volume Activity; Change in Corporate Income Tax Rate.